Waterscapes - Baviskar, Amita (ed.) (Ranikhet, 2007)
As a resource central to life and livelihood, water has always been at the centre of intense social action. Conflict and cooperation around water involve not only claims to a material resource but also assertions of cultural meanings. The contours of such collective action have radically changed in recent years: gigantic state projects such as large dams now occur alongside water markets and privatized supply systems. In the process, the communities that stake claims to water are also being refashioned. As social relations and institutional arrangements change, analyses of hydro-politics become all the more urgently relevant. Waterscapes examines this fluid, fast-changing terrain by using the analytical framework of cultural politics to examine questions of power and inequality, conflicts and compromises around water. It reflects the growing recognition that managing water, as much as land and biomass, is going to be a critical challenge for future economic growth and ecological sustainability. This challenge demands rigorous research into the political economy of water in the global South. Waterscapes is a major contribution by anthropologists, historians and sociologists, leading scholars in the field, who bring original ethnographic and archival research to bear on the cultural politics of a key natural resource. This book is essential reading for everyone interested in the politics of environment and development.
Keywords: Natural resources